Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.antiviral.2017.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin inhibits Zika and chikungunya virus infection by inhibiting cell binding

Abstract: Several compounds extracted from spices and herbs exhibit antiviral effects in vitro, suggesting potential pharmacological uses. Curcumin, a component of turmeric, has been used as a food additive and herbal supplement due to its potential medicinal properties. Previously, curcumin exhibited antiviral properties against several viruses, including dengue virus and hepatitis C virus, among others. Here, we describe the antiviral effect of curcumin on Zika and chikungunya viruses, two mosquito-borne outbreak viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
228
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 286 publications
(238 citation statements)
references
References 24 publications
6
228
0
4
Order By: Relevance
“…After incubation at 37 • C for 2 h, the plaque assay was performed, and the plaques were visualized as described above. Curcumin, a reported antiviral drug (Mounce et al, 2017), was included as positive control. The percent inhibition by the montelukast was calculated, and the 50% inhibitory concentration (IC50) value was determined by using the software CalcuSyn (Chou and Talalay, 1984).…”
Section: Plaque Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…After incubation at 37 • C for 2 h, the plaque assay was performed, and the plaques were visualized as described above. Curcumin, a reported antiviral drug (Mounce et al, 2017), was included as positive control. The percent inhibition by the montelukast was calculated, and the 50% inhibitory concentration (IC50) value was determined by using the software CalcuSyn (Chou and Talalay, 1984).…”
Section: Plaque Assaymentioning
confidence: 99%
“…Erythromycin estolate was also found to effectively inhibit ZIKV infection by disrupting the integrity of the viral membrane . ZINC33683341 and curcumin also inhibit infection of ZIKV by disturbing the interaction between virions and cells (Delvecchio et al, 2016;Fernando et al, 2016;Li et al, 2017b;Mounce et al, 2017). Nanchangmycin, one of the antibiotics against gram-positive bacteria, inhibited ZIKV infection through blocking clathrinmediated endocytosis (Rausch et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…We further carefully investigated the inhibition mechanism of the best antiviral agent, Cur‐CQDs‐180, against EV71, although elucidating the exact molecular interactions of the specific functional groups of CQDs and EV71 virions is difficult. Previous studies have demonstrated that antiviral curcumin could interact directly with many proteins, such as DNA polymerase, cell survival proteins, focal adhesion kinase, proteasome, thioredoxin reductase, protein kinase, lipoxygenase, carrier proteins, and tubulin . Therefore, in addition to blocking the viral attachment, the pleiotropic activities of curcumin against viral infection have been demonstrated to emanate from its multiple functions pertaining to a wide range of molecular targets, such as transcription regulation, the activation of intracellular signaling cascades, and the promotion of antioxidative activity.…”
Section: Resultsmentioning
confidence: 96%
“…In addition, it has been reported that curcumin acts against coxsackievirus B3 by reducing viral RNA expression and protein synthesis through dysregulation of the ubiquitin‐proteasome system (UPS) . A recent study revealed that curcumin inhibits arthropod‐borne viral infection with Zika and chikungunya viruses by interrupting the binding of viruses on the cell surface . Another study indicated that a high dosage of curcumin exhibited antiapoptotic ability at the early stage of viral infection of EV71 .…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin is the principal compound derived from the rhizome of Curcuma longa . Curcumin and curcuminoids have gained outstanding interest due to their therapeutic properties in neuroprotection, cancer prevention, arthritis and inflammation among many other purported properties . Structurally, curcumin and curcuminoids are heptanoids characterized by a β‐diketone chemical functionality .…”
Section: Introductionmentioning
confidence: 99%